BCL-2 inhibition in AML: an unexpected bonus? - Konopleva, Marina (Blood, 2018)
B-cell lymphoma 2 (BCL-2) was discovered at the breakpoint of the t(14;18) in follicular lymphoma >30 years ago. Although inhibition of BCL-2 first proved valuable in lymphoid malignancies, clinical progress in myeloid malignancies lagged. Here, we summarize the basic biology and preclinical results that spurred clinical BCL-2 inhibition in acute myeloid leukemia (AML). Response rates and toxicity for venetoclax in combination with standard AML agents, such as azacitidine, decitabine, and low-dose cytarabine, compare favorably with conventional induction chemotherapy. Durability of response requires further study.